A magnetotelluric investigation of the Scandinavian Caledonides in western Jämtland, Sweden, using the COSC borehole logs as prior information. Issue 3 (5th December 2016) - Yan, Ping; Garcia Juanatey, Maria A.; Kalscheuer, Thomas; Juhlin, Christopher; Hedin, Peter; Savvaidis, Alexandros; Lorenz, Henning; Kück, Jochem
Summary: In connection with the Collisional Orogeny in the Scandinavian Caledonides (COSC) project, broad-band magnetotelluric (MT) data were acquired at 78 stations along a recent ca . 55-km-long NW–SE directed reflection seismic profile (referred to as the COSC Seismic Profile; CSP), with the eastern end located ∼30 km to the west of the orogenic Caledonian front. The MT component of the project aims at (i) delineating the highly conductive (∼0.1 Ω ⋅ m) alum shales that are associated with an underlying main décollement and (ii) calibrating the MT model to borehole logs. Strike and distortion analyses of the MT data show a 3-D structure in the western 10 km of the profile around the 2.5 km deep COSC-1 borehole (IGSN: ICDP5054EHW1001) and a preferred strike angle of N34°E in the central and eastern parts of the profile. 2-D modelling of MT impedances was tested using different inversion schemes and parameters. To adjust the resistivity structure locally around the borehole, resistivity logging data from COSC-1 were successfully employed as prior constraints in the 2-D MT inversions. Compared with the CSP, the model inverted from the determinant impedances shows the highest level of structural similarity. A shallow resistor (>1000 Ω ⋅ m) in the top 2–3 km depth underneath the western most 10 km of the profile around COSC-1 corresponds to a zone of high seismic reflectivity, and a boundary at less than 1 km depth where the resistivity decreases rapidly from >100 to <1 Ω ⋅ m in the central and eastern parts of the profile coincides with the first seismic reflections. The depth to this boundary is well constrained as shown by 1-D inversions of the MT data from five selected sites and it decreases towards the Caledonian front in the east. Underneath the easternmost part of the profile, the MT data show evidence of a second deeper conductor (resistivity <1 Ω ⋅ m) at >3 km depth. Based upon the COSC-1 borehole logs, the CSP reflection seismic image, and the surface geologic map, the MT resistivity models were interpreted geologically. In the vicinity of COSC-1, the resistor down to 2–3 km depth pertains to the metamorphic Middle Allochthon. The up to 1000-m-thick shallow resistor in the central and eastern parts of the profile is interpreted to overly an imbricated unit at the bottom of the Lower Allochthon that includes the alum shales. In the MT resistivity model, the 300–500 m thick imbricated unit masks the main Caledonian décollement at its bottom. A second possible interpretation, though not favoured here, is that the décollement occurs along a much deeper seismic reflection shallowing from 4.5 km depth in the west to ∼600 m depth in the east. An additional borehole (COSC-2) is planned to penetrate the Lower Allochthon and the main décollement surface in the central part of the profile and can provide information to overcome this interpretational ambiguity. Using a synthetic study, we evaluate how resistivity logs from COSC-2 can improve the 2-D inversion model.